Rainwater Management through Watershed Approach - Dohare, D.D. (Journal of Soil and Water Conservation, 2022)
Rainfed agriculture occupying 68% of India’s cultivated area and supporting 40% of human and 60% of livestock population, produces 44% of food requirements and thus playing a critical role in India’s food security. Even when the full irrigation potential of 139.5 m.ha realized by 2050, agriculture in 75 m.ha will continue to be solely dependent on rainfall. Since the productivity in irrigated areas is reaching a plateau, bulk of rising food demand in the country has to be met through enhanced productivity of rainfed lands. Physical and biological measures that would ensure water harvesting and storage is discussed in this paper.